Ways To Adjust Economic Culture to The Requirements of Society Economy. - Ibragimova Gulchehra Tokhirovna (Euro Asian Journal Publishing, 2024)
The article reveals the nature of internal and external factors associated with human economic culture, classifies their rational use, and also discusses issues of preventing economic costs and reducing their impact on the green economy while complying with the requirements of the green economy
Keywords: Personal economic culture; personal economic security; internal and external factors of personal economic culture